An UWB microstrip monopole antenna for breast tumor detection. Issue 1 (18th November 2014) - Kahar, Manisha; Ray, Arup; Sarkar, Debashree; Sarkar, P. P
ABSTRACT An ultrawideband (UWB) monopole antenna is designed for microwave breast imaging on a heterogeneous breast model. Antenna parameters are studied on the breast model for near and far proximity of the antenna from the breast skin. High current density has been observed for all positions and sizes of deep seated and superficial tumors keeping specific absorption rate (SAR) within limits on surrounding tissues and skin. Features of UWB and safe acceptable SAR make the antenna suitable for its intended application. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:49–54, 2015